The Influence of Care Coordination on Patients With Special Health Care Needs in a Pediatric Residency Continuity Clinic - Zohra Moeenuddin MD; Caroline Kim-Kupfer MD; Erica Owchar MD; Joshua Baker DO; Amy Duffield MSW, LCSW; Thomas Santoro MD (SAGE Publishing, 2019)
This study evaluates the influence of comprehensive health care coordination for children with special health care needs (CSHCN) in a resident continuity clinic. CSHCN patients were identified from 2 resident continuity panels. Patients were eligible with a score of 2 or greater on the CSHCN screener. Interventions included extended appointment times, a binder, and direct phone access to the social worker who facilitated follow-up appointment scheduling. Data measured included completed and no-show visits for primary care and subspecialty appointments, hospitalization and emergency department visits, use of binders, and parent satisfaction surveys. Patients with a baseline CSHCN screener score ≥4 were 15.6 times more likely to keep their appointment after enrollment ( P = .0035). Mental health no-show visits decreased significantly ( P < .0001). The utilization of components of comprehensive team-based care coordination, even with limited resources, can improve the delivery of health care for children with complex medical needs and mental health disorders in a resident-based clinic.